Open versus robotic-assisted laparoscopic posterior component separation in complex abdominal wall repair. Issue 3 (24th June 2022) - Dewulf, Maxime; Hiekkaranta, Juha M; Mäkäräinen, Elisa; Saarnio, Juha; Vierstraete, Maaike; Ohtonen, Pasi; Muysoms, Filip; Rautio, Tero
Abstract: Background: Transversus abdominis release (TAR) is a surgical technique used in the treatment of complex ventral hernias. The aim of this study was to compare outcomes of open (oTAR) versus robotic-assisted (rTAR) posterior component separation by TAR. Methods: Consecutive patients at two European hernia centres who underwent bilateral TAR were included. The primary endpoint was the duration of postoperative hospital stay. Results: Data from 90 rTAR and 79 oTAR operations were evaluated. Patient demographics were similar between groups in terms of age, sex, BMI, and co-morbidities. There were more smokers, and hernias were larger in the oTAR group (width 8.7 cm versus 10.0 cm; P  = 0.031, length 11.6 cm versus 14.1 cm; P  = 0.005). Duration of postoperative hospital stay was significantly shorter in the rTAR group (3.4 days versus 6.9 days; P  < 0.001). Short-term serious complications (Clavien–Dindo grade III and above) were more frequent (20.3 per cent versus 7.8 per cent; P  = 0.018), and there were more surgical site infections (12.7 per cent versus 3.3 per cent; P  = 0.010) in the oTAR group. During a median follow-up of 19 months in the rTAR group and 43 months in the oTAR group, reoperation (4.4 per cent versus 8.9 per cent; P  = 0.245), and recurrence rates (5.6 per cent versus 5.1 per cent; P  > 0.009) were similar. Conclusion: Patients with ventral incisional hernias who undergo bilateral rTAR had significantly shorter postoperative hospital stays and fewer short-term complications compared with patients undergoing bilateral oTAR. Abstract : In this retrospective European multicentre study evaluating surgical treatment of 169 patients with a complex ventral incisional hernia, robotic-assisted laparoscopic transversus abdominis release results in a significant decrease in duration of postoperative hospital stay, and short-term postoperative complications when compared with open transversus abdominis release.